A Review Paper on Blockchain for Supply Chain Anti-Counterfeiting - Kedar, Athrav; Waje, Komal; Ghuge, Shravani; Lahare, Prasad (International Journal of Computer Sciences and Engineering, 2024)
Counterfeit goods pose a significant threat to the product manufacturing industries, directly impacting sales and profits. To counteract this issue, blockchain technology is proposed as a means to prevent product counterfeiting across the supply chain. With blockchain, consumers no longer need to rely on trusted third parties to verify the source and authenticity of purchased goods. Blockchain technology ensures that data is tamper-resistant, as it employs a decentralized, distributed, and digital ledger that stores transactional records, known as blocks, across multiple networks. This immutable characteristic of blockchain ensures that no changes can be made to one block without altering subsequent blocks. In this paper, a counterfeit product detection system is proposed, leveraging barcode readers in conjunction with a Blockchain-Based Management (BCBM) system. The system stores product details and unique product codes in a blockchain database and verifies the authenticity of the product by matching the customer-provided code with the entries in the blockchain. If a match is found, the consumer is notified of the product’s authenticity; otherwise, the system collects information on the origin of the counterfeit product to identify the manufacturer.